1992
DOI: 10.1007/bf01303016
|View full text |Cite
|
Sign up to set email alerts
|

High-spin states in165Hf

Abstract: High-spin states in 165Hf, populated in the 13~176 5n) reaction, were investigated using the Berkeley HERA 7-ray spectrometer array. The previously known level scheme of 165Hf is appreciably extended. Intrinsic configurations, band crossing frequencies and aligned angular momenta are interpreted within the frame-work of the cranked shell model. It is suggested that the alignments of the second neutron pair and of the first proton pair in ~65Hf occur at tacos0.44 MeV and g0.48 MeV, respectively. The systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
0
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 13 publications
3
0
0
Order By: Relevance
“…In addition, a similar deviation was noted for the πh 11/2 νE structure in the isotone 164 Lu [15]. A high-frequency crossing is present near 0.46 MeV, likely associated with the CD crossing (alignment of the third and fourth lowest i 13/2 quasineutrons) because a similar crossing was identified [9] near this frequency in the νE configuration of 165 Hf [see Fig. 3(b)].…”
supporting
confidence: 69%
See 1 more Smart Citation
“…In addition, a similar deviation was noted for the πh 11/2 νE structure in the isotone 164 Lu [15]. A high-frequency crossing is present near 0.46 MeV, likely associated with the CD crossing (alignment of the third and fourth lowest i 13/2 quasineutrons) because a similar crossing was identified [9] near this frequency in the νE configuration of 165 Hf [see Fig. 3(b)].…”
supporting
confidence: 69%
“…The crossing frequency of ∼0.33 MeV, and the alignment gain of ∼8h, in band 1 tracks those observed in the νi 13/2 structure in 165 Hf [9] and the πh 11/2 νi 13/2 bands of 168,170 Ta [2,3]. This crossing is typically referred to as the BC alignment, where the second and third lowest i 13/2 quasineutrons align.…”
supporting
confidence: 64%
“…The measured proton crossing frequencies and the magnitude of the aligned angular momenta for the lowest positive-and negative-parity bands in the Hf isotopes are summarized in Table IV. In an earlier study [26], Neffgen et al suggested that these crossing frequencies should also increase with increasing neutron number, as the heavier Hf isotopes in this mass region are characterized by larger quadrupole deformation [27,28]. The data in Table IV, spanning a chain of eleven Hf isotopes, provide solid evidence for such an effect.…”
Section: A Bands 1 Andsupporting
confidence: 48%